Strengthening General Health Professions through the Integration of Educational Interventions and Traditional Health Services - Cheptanari Nicoleta; Aldieo Hartman Fahreza (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aims to investigate the integration of educational interventions with traditional health services in Tanjung Raya Village, Way Kanan, to enhance community knowledge and align practices with Fiqh Siyasah principles, ensuring culturally and religiously compliant healthcare. Methodology: A qualitative field research design was employed, collecting primary data through observations, interviews with traditional practitioners, community leaders, and residents, and document reviews. Data were processed using editing, reconstruction, and systematization, and analyzed through qualitative content analysis to identify themes and patterns in traditional health practices. Main Findings: Traditional health services remain widely utilized and trusted. Educational interventions improved understanding of safe and permissible practices, increased compliance with Fiqh Siyasah, and encouraged a balance between traditional and modern health knowledge. Community trust, affordability, and cultural familiarity remain key factors in service utilization. Novelty/Originality of this study: The study integrates empirical, cultural, and religious perspectives to address a gap in previous research by combining health education with traditional practices under Fiqh Siyasah. This approach offers a novel model for culturally sensitive and legally compliant health interventions in rural communities, advancing knowledge on integrating tradition and modern education.